A parametric study of implementing green roofs to improve building energy performance in tropical climate - Moreno Agnieszka (EDP Sciences, 2021)
Energy is one of the most involving issues, its use, the way to spread it, and how to reduce its consumption. Because of this, it is important to opt for solutions that determine the final use of energy. The feasibility study of vegetation applied to green roofs for buildings would be a favorable solution to stop absorbing the heat that we consume daily, and at the same time, we produce. Thus, this research aims to evaluate the implementation of generic vegetation on the roof of buildings in Panama, in terms of electricity consumption for cooling, through dynamic simulation. For this, a parametric analysis was performed through the DesignBuilder program, where four plants suitable for the climate of Panama and resistant to solar radiation, high temperatures, and humidity were chosen, which were Tradescantia spathacea Sw., Sansevieria sp., Aloe Vera, and Arachis hypogaea. Employing passive and mechanical mode simulations with 24-hour irrigation systems, it was possible to observe how the temperature inside the building and the heat gains through the roof decrease. This led us to determine the most important parameters of the vegetation layer: plant height, leaf area index (LAI), leaf reflectivity, and stomatal resistance.